PENGARUH PENGUNGKPAN MANAJEMEN RISIKO TERHADAP FINANCIAL DITRESS DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI PADA SUB SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 - 2019 - Julianti Ria; Haryetti Haryetti; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of risk management on financial difficulties by mediating good corporate governance. The independent variable in this study is risk management using the COSO working paper. The dependent variable is financial difficulties. Financial difficulties in this study using the Olhson model. And the mediating variable in this study is good corporate governance. The population in this study is the basic and chemical industry sub-sector which is officially listed on the Indonesia Stock Exchange for the period 2015 – 2019 as many as 73 companies. The data is reprocessed according to the needs of the model used. The analytical method used in this research is path analysis. The sampling technique chosen was purposive sampling method. The sample in this study were 45 companies. The results of this study indicate that; First, risk management has a significant positive effect on good corporate governance; Second, risk management has a significant positive effect on financial difficulties; Third, good corporate governance has a significant positive effect on financial difficulties; Fourth, good corporate governance mediates the management of financial risk management.Keywords: Disclosure of Risk Management, Good Corporate Governance, Financial Distress